High-adhesion quick-drying inorganic zinc silicate shop primer and preparation method thereof
Through the synergistic effect of modified zinc powder and graphite powder, a four-dimensional bonding network is formed, which solves the problem of insufficient adhesion and drying speed of the primer in the inorganic zinc silicate workshop, and achieves efficient and stable coating performance to meet the needs of large-scale rapid construction.
Patent Information
- Application Number
- CN202510909522.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-02
- Publication Date
- 2025-08-22
AI Technical Summary
The existing inorganic zinc silicate workshop primer has shortcomings in adhesion and drying speed, especially in complex environments or external force impacts, and the drying speed is slow, which cannot meet the needs of large-scale rapid construction.
Components such as modified zinc powder, modified graphite powder, sodium silicate solution, quick-drying agent, adhesion accelerator, heat-resistant filler, dispersant and defoaming agent are used to prepare high adhesion fast-drying inorganic zinc silicate workshop primer through specific proportions and processes to form a four-dimensional bonding network to jointly improve adhesion and drying speed.
It significantly improves the adhesion and drying speed of the inorganic zinc silicate workshop primer, meets the needs of high temperature stability and welding process, and improves construction efficiency and coating quality.
Smart Images

Figure BDA0005479631280000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of coating preparation, and in particular to a high-adhesion, fast-drying inorganic zinc silicate shop primer and a preparation method thereof. Background Art
[0002] Inorganic zinc silicate shop primers are widely used for metal surface protection in industries such as shipbuilding, bridge construction, and the petrochemical industry due to their excellent corrosion and solvent resistance and good heat resistance. However, existing inorganic zinc silicate shop primers have several shortcomings. On the one hand, the adhesion of the primer needs to be improved. In some complex environments or when subjected to external forces, the coating is prone to flaking and peeling, which affects the protective effect and service life. On the other hand, the drying speed is slow. Especially in environments with high humidity or low temperature, excessive drying time can lead to low construction efficiency and increased construction costs, making it unable to meet the needs of large-scale and rapid construction.
[0003] Various approaches have been used to improve the performance of inorganic zinc silicate shop primers. To increase drying speed, a common approach is to increase the solvent's evaporation rate, for example by using a more volatile solvent to accelerate the primer's drying. To enhance adhesion, organic resin modification is often employed, whereby the addition of organic resins improves the primer's ability to bond to the metal surface. These methods can indeed improve some of the primer's properties to a certain extent.
[0004] However, existing methods have significant drawbacks. While increasing the solvent evaporation rate can speed up drying, it can easily cause the coating to wrinkle or zinc powder to settle, affecting coating quality. Relying on organic resin modification to enhance adhesion can reduce the coating's weather resistance and zinc powder utilization. Furthermore, existing inorganic zinc silicate workshop primers themselves lack adhesion, making the coating prone to flaking and peeling in complex environments or when subjected to external forces. They also dry slowly, resulting in low construction efficiency in environments with high humidity or low temperatures, making them unable to meet the needs of large-scale, rapid construction. Summary of the Invention
[0005] In order to improve the adhesion and drying speed of inorganic zinc silicate shop primer, the present application provides a high-adhesion fast-drying inorganic zinc silicate shop primer and a preparation method thereof.
[0006] In the first aspect, the present application provides a high-adhesion, fast-drying inorganic zinc silicate shop primer that adopts the following technical solution: A high-adhesion, quick-drying inorganic zinc silicate shop primer is prepared from raw materials comprising, by weight, 30-50 parts of modified zinc powder, 1.5-2.5 parts of modified graphite powder, 20-35 parts of sodium silicate solution, 5 parts of α-phase nano-Al2O3, 3-4 parts of a quick-drying agent, 3-5 parts of an adhesion promoter, 2.5-3.5 parts of a heat-resistant filler, 1-2 parts of a dispersant, 0.6-1.0 parts of a defoaming agent, and 10-20 parts of a diluent. The quick-drying agent comprises zinc naphthenate, EDTA, and titanium isopropoxide, and the mass ratio of the zinc naphthenate, EDTA, and titanium isopropoxide is 1:(0.2-0.3):(0.45-0.55).
[0007] By employing this technical solution, modified zinc powder serves as the primary rust-proofing component, forming a sacrificial anode within the coating and providing electrochemical protection for the metal substrate. Modified graphite powder acts as a high-temperature lubricant, reducing the coating's thermal expansion coefficient and ensuring compatibility with the steel substrate. Sodium silicate solution, a film-forming agent, forms an inorganic silicate film upon evaporation, exhibiting excellent chemical stability and corrosion resistance. α-phase nano-Al₂O₃, with its small size effect and high activity, can fill gaps in the coating, further enhancing its density and adhesion. The zinc naphthenate, EDTA, and titanium isopropoxide in the fast-drying agent work synergistically in specific mass ratios. Zinc naphthenate promotes solvent evaporation, EDTA complexes metal ions, and titanium isopropoxide participates in the film-forming reaction, accelerating curing. Together, these factors significantly increase the primer's drying speed. The adhesion promoter, through its active ingredients, improves the interfacial bonding between the primer and the substrate, enhancing adhesion. Heat-resistant fillers enhance the primer's heat resistance, ensuring its stability in high-temperature environments. Dispersants help evenly disperse the ingredients, preventing agglomeration and ensuring the stability of the primer's performance. Defoamers eliminate bubbles generated during preparation and application, improving the smoothness and quality of the coating. Diluents adjust the primer's viscosity, facilitating application. These ingredients work synergistically to simultaneously improve the adhesion and drying speed of the inorganic zinc silicate shop primer, overcoming the shortcomings of existing primers, which suffer from insufficient adhesion and slow drying speeds.
[0008] In a specific embodiment, the modified zinc powder is prepared by pre-dispersing 30-50 parts of zinc powder and 0.5-1.5 parts of KH-560 in an ethanol solution, stirring and mixing at 60° C., filtering and drying to obtain a modified zinc powder coated with silane.
[0009] Silane modification is typically used to improve filler dispersibility, but the inventors discovered that the zinc powder in this application, modified with KH-560, exhibited unexpectedly significantly improved adhesion and corrosion resistance. This is likely due to the silane forming a steric barrier on the zinc powder surface after modification with the KH-560 silane coupling agent, preventing the zinc powder from agglomerating due to van der Waals forces. In the primer, some hydroxyl groups on the surface of the zinc powder react with the Si-OH groups of the silicate to form "Zn-O-Si" bonds, anchoring the zinc powder to the silicate skeleton. After the primer is coated on the steel substrate, the epoxy groups of KH-560 react with the hydroxyl groups on the surface of the steel substrate to form a "substrate-silane-zinc powder" bonding network, allowing the primer to anchor the silicate skeleton based on the epoxy groups on the substrate surface, and anchor the zinc powder based on the silicate skeleton, thereby making the coating dense, the zinc powder stacking reasonably distributed, and the uniformity deviation of the zinc content in the subsequent coating reduced. After the subsequent primer is coated on the steel substrate, the interfacial bonding strength between the zinc powder and the substrate is greatly improved. Therefore, the selection of a specific epoxysilane coupling agent to modify the zinc powder in silicate coatings unexpectedly achieved a significant improvement in adhesion and corrosion resistance.
[0010] In a specific embodiment, the modified graphite powder is prepared by pre-dispersing 1-3 parts of graphite powder and 0.45-0.65 parts of KH-560 in an ethanol solution, stirring and mixing at 60° C., filtering and drying to obtain modified graphite powder coated with silane.
[0011] By adopting the above technical solution, the layered structure of graphite forms a micro-sliding interface in the coating, which can reduce the internal stress of the coating. However, the intrinsic thermal expansion coefficient of graphite is significantly different from that of the steel substrate. After the surface is coated with silane, the "silane layer buffer" reduces the thermal expansion difference, reducing thermal stress cracking between the coating and the substrate at high temperatures, improving the thermal expansion coefficient of the primer coating on the steel substrate and the steel substrate. It also reduces the thermal stress during welding between steel substrates and reduces the risk of peeling and flaking of the primer coating. The epoxy group of silane reacts with the Si-OH group of silicate, "embedding" the graphite powder into the silicate skeleton, forming a four-dimensional bonding network of "substrate-silicate-graphite-zinc powder", which improves the flexibility and impact resistance of the primer coating on the steel substrate.
[0012] In a specific embodiment, the modulus of the sodium silicate in the sodium silicate solution is 3.5-3.8.
[0013] By adopting the above technical solution, the modulus of sodium silicate, i.e. the molar ratio of SiO2 / Na2O, directly affects the hydrolysis and condensation reaction rate and film-forming properties of silicate. 2- Higher concentrations generate more Si(OH)4 through hydrolysis, resulting in more intense condensation reactions and faster film formation. The Si-O bond energy in the skeleton formed by high modulus silicates is higher, significantly improving chemical corrosion resistance and water resistance. In a specific embodiment, the adhesion promoter includes KH-560 and E-44 epoxy resins, and the mass ratio of the KH-560 to E-44 epoxy resins is 3:1.
[0014] The inventors discovered that compounding KH-560 and E-44 epoxy resins in this mass ratio synergistically improves interfacial strength. The epoxy groups of KH-560 react with the hydroxyl groups of the steel substrate to form a "substrate-silane" bonding layer, while the hydroxyl groups (-OH) of the E-44 epoxy resin react with the Si-OH of the silicate to form a "silicate-resin" crosslinking layer, which then doubles the locking between the zinc powder and the substrate. Furthermore, the low surface tension of KH-560 complements the high viscosity of E-44, preventing delamination between the resin and silicate, improving the compatibility of the resin and silicate and reducing interfacial defects. At the same time, the epoxy groups of E-44 and KH-560 synergistically crosslink to form a network structure, reducing cure shrinkage, reducing internal stress in the coating, and improving the adhesion of the primer.
[0015] In a specific embodiment, the heat-resistant filler is ZrO2 and zinc borate, and the mass ratio of ZrO2 to zinc borate is 2:1.
[0016] The inventors discovered that compounding ZrO2 and zinc borate in this mass ratio synergistically improves heat resistance. On the one hand, ZrO2 forms a stable tetragonal phase at high temperatures, thereby inhibiting the high-temperature decomposition of the silicate skeleton. On the other hand, zinc borate decomposes at high temperatures to produce B2O3, which reacts with Na2O in the sodium silicate solution to form a glassy layer of Na2B4O7, which covers the surface of the zinc powder and prevents zinc oxidation. ZrO2 and zinc borate also synergistically reduce the thermal conductivity of the coating, reducing the transfer of high-temperature heat to the substrate, thereby improving the thermal insulation performance of the coating. Furthermore, the cost of the composite filler of zinc borate and ZrO2 is only one-third of that of traditional rare earth heat-resistant fillers, significantly improving the cost-effectiveness.
[0017] In a specific embodiment, the dilution solvent includes propylene glycol methyl ether acetate and dimethyl carbonate, and the mass ratio of the propylene glycol methyl ether acetate to the dimethyl carbonate is 2:1.
[0018] The inventors discovered that by mixing a slow-drying solvent, propylene glycol methyl ether acetate, with a fast-drying solvent, dimethyl carbonate, in a 2:1 ratio, the evaporation rate can be controlled, keeping the mixed solvent's evaporation rate (i.e., coat-4 cup leveling time) within 15-20 seconds, thus avoiding the "orange peel" effect caused by excessive solvent evaporation. Furthermore, the polarities of propylene glycol methyl ether acetate and dimethyl carbonate are close to those of silicates, ensuring the diluent's solubility in silicates. Furthermore, the low toxicity of dimethyl carbonate replaces traditional benzene solvents, significantly reducing the VOC content and thus improving the primer's environmental friendliness.
[0019] In a specific embodiment, the dispersant is a polycarboxylate dispersant.
[0020] By adopting the above technical solution, the dispersing effect of polycarboxylate (PAAS) is reflected in the following aspects: electrostatic steric stabilization: the -COO- group of PAAS is adsorbed on the surface of zinc powder / Al2O3 to form a negative charge layer, which prevents agglomeration by repulsion of like charges; steric protection: the long polycarboxylic acid chain of PAAS stretches on the filler surface, forming a physical barrier that hinders the approach of filler particles; pH adaptability: PAAS dissociates more fully in an alkaline environment, the adsorption density is improved, and the dispersion effect is better than that of traditional anionic dispersants.
[0021] In a specific embodiment, the defoaming agent is an organosilicon defoaming agent.
[0022] By adopting this technical solution, the surface tension of silicone is much lower than that of water and silicate solutions, allowing it to spread quickly on the bubble surface. Due to the surface tension difference, the bubble liquid film is stretched and thinned, eventually rupturing. Furthermore, due to the poor compatibility of silicone with silicate, silicone only accumulates on the bubble surface and is insoluble in the system, thus preventing secondary foaming.
[0023] In a second aspect, the present application provides a method for preparing a high-adhesion, fast-drying inorganic zinc silicate shop primer, comprising the following steps: S1. Premixing of composite fillers: Add modified graphite powder, α-phase nano-Al2O3, heat-resistant filler, and dispersant into a high-speed disperser, premix and disperse vigorously to obtain premixed fillers; S2: Preparation of silicate-quick-drying agent system: Add zinc naphthenate and EDTA to the sodium silicate solution, stir and mix at 50°C, add titanium isopropoxide dropwise, and heat to 60°C to react to obtain a viscous silicate system solution; S3, mixing: add the premixed filler into the silicate system viscous liquid and mix well, then add KH-560 and E-44 epoxy resins and mix well, then add the organosilicon defoamer to disperse vigorously; S4. Paint mixing: Add diluent solvent to adjust the viscosity to 18-22 seconds (25°C) for 4 cups.
[0024] By adopting the above technical solution, the preparation steps are carried out in a progressive manner, following the sequence of "filler pretreatment-chemical catalysis-interface enhancement-viscosity control." First, modified graphite powder, α-phase Al2O3, and heat-resistant filler are pre-dispersed with PAAS and then dispersed at high speed and force to ensure uniform filler distribution and prevent secondary agglomeration during subsequent mixing. Zinc naphthenate, EDTA, and titanium isopropoxide are then added sequentially to the sodium silicate solution, ensuring the catalytic reaction proceeds through the hydrolysis-condensation-film formation stages. Next, after the premixed filler is added to the silicate system, KH-560 and E-44 epoxy resins are added sequentially, utilizing the Si-OH groups of the silicate to react with the epoxy groups of both to form a "filler-silicate-resin" network. High-speed dispersion is then performed to accelerate the reaction. Finally, a diluent solvent is added to adjust the viscosity to avoid uneven dispersion caused by premature dilution. This preparation step significantly improves production efficiency compared to traditional processes, and enhances batch stability of coating performance, ultimately resulting in a high-adhesion, fast-drying inorganic zinc silicate shop primer.
[0025] In summary, this application includes at least one of the following beneficial technical effects: 1. This application significantly improves the drying efficiency through the triple synergistic mechanism of "Lewis acid catalysis + alkaline environment maintenance + solvent volatilization acceleration". 2+ ) acts as an inorganic Lewis acid to catalyze the hydrolysis of silicates to generate more Si-OH groups; EDTA chelates metal ions and neutralizes the H released by the reaction. + , maintaining a weakly alkaline environment of pH = 10.5-11.0, accelerating the Si-O-Si condensation reaction; titanium isopropoxide hydrolyzes to form TiO2 sol, which fills the silicate pores and reduces the surface tension, accelerating the volatilization of the solvent. The synergistic effect of the three effectively improves the drying efficiency of the inorganic zinc silicate workshop primer, thereby meeting the efficient production needs of the workshop; 2. This application constructs a four-dimensional bonding network of "substrate-silane-zinc powder / graphite-silicate-resin" through the dual design of "filler surface modification + dual interface enhancer". The epoxy group of the modified zinc powder reacts with the hydroxyl group of the steel substrate to undergo an epoxy ring-opening reaction, and the alkoxy group reacts with the Si-OH of the silicate to form a "Zn-O-Si" bond, anchoring the zinc powder to the substrate; the flexible carbon chain of the modified graphite powder fills the gaps in the filler and reduces internal stress; the epoxy group of KH-560 reacts with the hydroxyl group of the steel substrate, and the E-44 epoxy resin forms a three-dimensional network structure after curing, mechanically anchoring the zinc powder and the silicate. The synergistic effect of the three can effectively prevent the coating from falling off and effectively improve the adhesion; 3. This application utilizes a composite design of "high-temperature stable filler + thermal expansion matching + welding protection" to simultaneously address high-temperature stability and welding burn issues. α-phase nano-Al₂O₃ fills the silicate pores, forming a dense Si-O-Al-O framework; ZrO₂ inhibits silicate decomposition; zinc borate coats the zinc powder surface, preventing oxidation; and modified graphite powder reduces the coating's thermal expansion coefficient. The synergistic effect of these three elements improves the thermal expansion coefficient's match with the substrate, meeting the requirements of high-temperature operating conditions and welding processes. DETAILED DESCRIPTION
[0026] The present application is further described in detail below with reference to the following examples and comparative examples: Some of the raw materials used in the preparation examples, embodiments and comparative examples: α-phase nano-Al2O3, brand: XT-080-1, purchased from Shanghai Xiangtian Nanomaterials Co., Ltd.; E-44 epoxy resin (CAS number: 25068-38-6, epoxy value: 0.41-0.47 mol / 100 g); polycarboxylate dispersant, brand: BYK-P105, purchased from BYK Additives (Shanghai) Co., Ltd. The raw materials used in the preparation examples, embodiments and comparative examples that are not otherwise specified are all conventional products that can be purchased commercially, and the unit "part" in the following preparation steps represents part by weight.
[0027] Preparation Example Preparation Example 1 The preparation steps of the modified zinc powder are as follows: 40 parts of zinc powder and 4 parts of KH-560 are added to 400 parts of ethanol solution for pre-dispersion, the mixture is heated to 60° C. and stirred for 30 minutes, and then filtered and dried to obtain the modified zinc powder with the surface coated with silane.
[0028] Preparation Example 2 Preparation steps of modified graphite powder: 2 parts of graphite powder and 0.05 parts of KH-560 are added to 20 parts of ethanol solution for pre-dispersion, heated to 60°C and stirred for 30 minutes, filtered and dried to obtain modified graphite powder with silane coated on the surface. Example
[0029] Example 1 S1. Premixing of composite fillers: Add 2 parts of modified graphite powder, 5 parts of α-phase nano-Al2O3, 3 parts of ZrO2, and 1.5 parts of polycarboxylate dispersant into a high-speed disperser, premix at 300 rpm for 5 minutes, and then disperse at 1500 rpm for 15 minutes. Prepare a premixed filler; S2: Preparation of silicate-quick-drying agent system: Add 2 parts of zinc naphthenate and 0.5 parts of EDTA to 27.5 parts of sodium silicate solution, stir at 50°C for 10 minutes, then dropwise add 1 part of titanium isopropoxide, heat to 60°C and react for 20 minutes to obtain a viscous silicate system solution; S3, mixing: add the silicate system viscous liquid to a high-speed disperser and mix it with the premixed filler, stirring at a speed of 800 rpm for 10 minutes; then add 3 parts of KH-560 and 1 part of E-44 epoxy resin, and disperse at a speed of 1200 rpm for 5 minutes; then add 0.8 parts of silicone defoamer and disperse at a speed of 1500 rpm for 3 minutes; S4. Paint adjustment: Add 10 parts of propylene glycol methyl ether acetate and 5 parts of dimethyl carbonate as a diluent, and the primer viscosity reaches -4 cups 18-22s (25°C).
[0030] Example 2 S1. Premixing of composite fillers: Add 2 parts of modified graphite powder, 5 parts of α-phase nano-Al2O3, 3 parts of zinc borate, and 1.5 parts of polycarboxylate dispersant into a high-speed disperser, premix at 300 rpm for 5 minutes, and then disperse at 1500 rpm for 15 minutes to prepare a premixed filler; S2: Preparation of silicate-quick-drying agent system: Add 2 parts of zinc naphthenate and 0.5 parts of EDTA to 27.5 parts of sodium silicate solution, stir at 50°C for 10 minutes, then dropwise add 1 part of titanium isopropoxide, heat to 60°C and react for 20 minutes to obtain a viscous silicate system solution; S3, mixing: add the silicate system viscous liquid to a high-speed disperser and mix it with the premixed filler, stirring at a speed of 800 rpm for 10 minutes; then add 3 parts of KH-560 and 1 part of E-44 epoxy resin, and disperse at a speed of 1200 rpm for 5 minutes; then add 0.8 parts of silicone defoamer and disperse at a speed of 1500 rpm for 3 minutes; S4. Paint adjustment: Add 10 parts of propylene glycol methyl ether acetate and 5 parts of dimethyl carbonate as a diluent, and the primer viscosity reaches -4 cups 18-22s (25°C).
[0031] Example 3 S1. Premixing of composite fillers: Add 2 parts of modified graphite powder, 5 parts of α-phase nano-Al2O3, 2 parts of ZrO2, 1 part of zinc borate, and 1.5 parts of polycarboxylate dispersant into a high-speed disperser, premix at 300 rpm for 5 minutes, and then disperse at 1500 rpm for 15 minutes to prepare a premixed filler; S2: Preparation of silicate-quick-drying agent system: Add 2 parts of zinc naphthenate and 0.5 parts of EDTA to 27.5 parts of sodium silicate solution, stir at 50°C for 10 minutes, then dropwise add 1 part of titanium isopropoxide, heat to 60°C and react for 20 minutes to obtain a viscous silicate system solution; S3, mixing: add the silicate system viscous liquid to a high-speed disperser and mix it with the premixed filler, stirring at a speed of 800 rpm for 10 minutes; then add 3 parts of KH-560 and 1 part of E-44 epoxy resin, and disperse at a speed of 1200 rpm for 5 minutes; then add 0.8 parts of silicone defoamer and disperse at a speed of 1500 rpm for 3 minutes; S4. Paint adjustment: Add 10 parts of propylene glycol methyl ether acetate and 5 parts of dimethyl carbonate as a diluent, and the primer viscosity reaches -4 cups 18-22s (25°C).
[0032] Example 4 S1. Premixing of composite fillers: Add 2 parts of modified graphite powder, 5 parts of α-phase nano-Al2O3, 2 parts of ZrO2, 1 part of zinc borate, and 1.5 parts of polycarboxylate dispersant into a high-speed disperser, premix at 300 rpm for 5 minutes, and then disperse at 1500 rpm for 15 minutes to prepare a premixed filler; S2: Preparation of silicate-quick-drying agent system: Add 2 parts of zinc naphthenate and 0.5 parts of EDTA to 27.5 parts of sodium silicate solution, stir at 50°C for 10 minutes, then dropwise add 1 part of titanium isopropoxide, heat to 60°C and react for 20 minutes to obtain a viscous silicate system solution; S3, mixing: add the silicate system viscous liquid into a high-speed disperser and mix it with the premixed filler. Stir at a speed of 800 rpm for 10 minutes. Then add 4 parts of KH-560 and disperse at a speed of 1200 rpm for 5 minutes. Then add 0.8 parts of silicone defoamer and disperse at a speed of 1500 rpm for 3 minutes. S4. Paint adjustment: Add 10 parts of propylene glycol methyl ether acetate and 5 parts of dimethyl carbonate as a diluent, and the primer viscosity reaches -4 cups 18-22s (25°C).
[0033] Example 5 S1. Premixing of composite fillers: Add 2 parts of modified graphite powder, 5 parts of α-phase nano-Al2O3, 2 parts of ZrO2, 1 part of zinc borate, and 1.5 parts of polycarboxylate dispersant into a high-speed disperser, premix at 300 rpm for 5 minutes, and then disperse at 1500 rpm for 15 minutes to prepare a premixed filler; S2: Preparation of silicate-quick-drying agent system: Add 2 parts of zinc naphthenate and 0.5 parts of EDTA to 27.5 parts of sodium silicate solution, stir at 50°C for 10 minutes, then dropwise add 1 part of titanium isopropoxide, heat to 60°C and react for 20 minutes to obtain a viscous silicate system solution; S3, mixing: add the silicate system viscous liquid to a high-speed disperser and mix it with the premixed filler. Stir at a speed of 800 rpm for 10 minutes. Then add 4 parts of E-44 epoxy resin and disperse at a speed of 1200 rpm for 5 minutes. Then add 0.8 parts of silicone defoamer and disperse at a speed of 1500 rpm for 3 minutes. S4. Paint adjustment: Add 10 parts of propylene glycol methyl ether acetate and 5 parts of dimethyl carbonate as a diluent, and the primer viscosity reaches -4 cups 18-22s (25°C).
[0034] Example 6 S1. Premixing of composite fillers: Add 2 parts of modified graphite powder, 5 parts of α-phase nano-Al2O3, 2 parts of ZrO2, 1 part of zinc borate, and 1.5 parts of polycarboxylate dispersant into a high-speed disperser, premix at 300 rpm for 5 minutes, and then disperse at 1500 rpm for 15 minutes to prepare a premixed filler; S2: Preparation of silicate-quick-drying agent system: Add 2 parts of zinc naphthenate and 0.4 parts of EDTA to 27.5 parts of sodium silicate solution, stir at 50°C for 10 minutes, then dropwise add 1.1 parts of titanium isopropoxide, heat to 60°C and react for 20 minutes to obtain a viscous silicate system solution; S3, mixing: add the silicate system viscous liquid to a high-speed disperser and mix it with the premixed filler, stirring at a speed of 800 rpm for 10 minutes; then add 3 parts of KH-560 and 1 part of E-44 epoxy resin, and disperse at a speed of 1200 rpm for 5 minutes; then add 0.8 parts of silicone defoamer and disperse at a speed of 1500 rpm for 3 minutes; S4. Paint adjustment: Add 10 parts of propylene glycol methyl ether acetate and 5 parts of dimethyl carbonate as a diluent, and the primer viscosity reaches -4 cups 18-22s (25°C).
[0035] Example 7 S1. Premixing of composite fillers: Add 2 parts of modified graphite powder, 5 parts of α-phase nano-Al2O3, 2 parts of ZrO2, 1 part of zinc borate, and 1.5 parts of polycarboxylate dispersant into a high-speed disperser, premix at 300 rpm for 5 minutes, and then disperse at 1500 rpm for 15 minutes to prepare a premixed filler; S2: Preparation of silicate-quick-drying agent system: Add 2 parts of zinc naphthenate and 0.6 parts of EDTA to 27.5 parts of sodium silicate solution, stir at 50°C for 10 minutes, then dropwise add 0.9 parts of titanium isopropoxide, heat to 60°C and react for 20 minutes to obtain a viscous silicate system solution; S3, mixing: add the silicate system viscous liquid to a high-speed disperser and mix it with the premixed filler, stirring at a speed of 800 rpm for 10 minutes; then add 3 parts of KH-560 and 1 part of E-44 epoxy resin, and disperse at a speed of 1200 rpm for 5 minutes; then add 0.8 parts of silicone defoamer and disperse at a speed of 1500 rpm for 3 minutes; S4. Paint adjustment: Add 10 parts of propylene glycol methyl ether acetate and 5 parts of dimethyl carbonate as a diluent, and the primer viscosity reaches -4 cups 18-22s (25°C).
[0036] Comparative Example Comparative Example 1 S1. Premixing of composite fillers: Add 2 parts of modified graphite powder, 5 parts of α-phase nano-Al2O3, 2 parts of ZrO2, 1 part of zinc borate, and 1.5 parts of polycarboxylate dispersant into a high-speed disperser, premix at 300 rpm for 5 minutes, and then disperse at 1500 rpm for 15 minutes to prepare a premixed filler; S2: Preparation of silicate-quick-drying agent system: Add 3.5 parts of zinc naphthenate to 27.5 parts of sodium silicate solution and stir at 50°C for 30 minutes to obtain a viscous silicate system liquid; S3, mixing: add the silicate system viscous liquid to a high-speed disperser and mix it with the premixed filler, stirring at a speed of 800 rpm for 10 minutes; then add 3 parts of KH-560 and 1 part of E-44 epoxy resin, and disperse at a speed of 1200 rpm for 5 minutes; then add 0.8 parts of silicone defoamer and disperse at a speed of 1500 rpm for 3 minutes; S4. Paint adjustment: Add 10 parts of propylene glycol methyl ether acetate and 5 parts of dimethyl carbonate as a diluent, and the primer viscosity reaches -4 cups 18-22s (25°C).
[0037] Comparative Example 2 S1. Premixing of composite fillers: Add 2 parts of modified graphite powder, 5 parts of α-phase nano-Al2O3, 2 parts of ZrO2, 1 part of zinc borate, and 1.5 parts of polycarboxylate dispersant into a high-speed disperser, premix at 300 rpm for 5 minutes, and then disperse at 1500 rpm for 15 minutes to prepare a premixed filler; S2: Preparation of silicate-quick-drying agent system: Add 3.5 parts of EDTA to 27.5 parts of sodium silicate solution and stir at 50°C for 30 minutes to obtain a viscous silicate system liquid; S3, mixing: add the silicate system viscous liquid to a high-speed disperser and mix it with the premixed filler, stirring at a speed of 800 rpm for 10 minutes; then add 3 parts of KH-560 and 1 part of E-44 epoxy resin, and disperse at a speed of 1200 rpm for 5 minutes; then add 0.8 parts of silicone defoamer and disperse at a speed of 1500 rpm for 3 minutes; S4. Paint adjustment: Add 10 parts of propylene glycol methyl ether acetate and 5 parts of dimethyl carbonate as a diluent, and the primer viscosity reaches -4 cups 18-22s (25°C).
[0038] Comparative Example 3 S1. Premixing of composite fillers: Add 2 parts of modified graphite powder, 5 parts of α-phase nano-Al2O3, 2 parts of ZrO2, 1 part of zinc borate, and 1.5 parts of polycarboxylate dispersant into a high-speed disperser, premix at 300 rpm for 5 minutes, and then disperse at 1500 rpm for 15 minutes to prepare a premixed filler; S2: Preparation of silicate-quick-drying agent system: 3.5 parts of titanium isopropoxide were added dropwise to 27.5 parts of sodium silicate solution, and stirred at 60°C for 30 minutes to obtain a viscous silicate system liquid; S3, mixing: add the silicate system viscous liquid to a high-speed disperser and mix it with the premixed filler, stirring at a speed of 800 rpm for 10 minutes; then add 3 parts of KH-560 and 1 part of E-44 epoxy resin, and disperse at a speed of 1200 rpm for 5 minutes; then add 0.8 parts of silicone defoamer and disperse at a speed of 1500 rpm for 3 minutes; S4. Paint adjustment: Add 10 parts of propylene glycol methyl ether acetate and 5 parts of dimethyl carbonate as a diluent, and the primer viscosity reaches -4 cups 18-22s (25°C).
[0039] Performance testing Take a small amount of the primer prepared in Examples 1-7 and Comparative Examples 1-3 and place them in corresponding beakers respectively. Observe the sedimentation of the primer powder after stirring. The time it takes for a 2 mm high transparent layer to appear on the top layer of the primer in the beaker is recorded as the construction time. The shorter the time, the faster the powder in the primer settles and the worse the construction performance.
[0040] Within the construction time, spray the primer into a film, controlling the wet film thickness to 20-26 microns and the dry film thickness to 15-20 microns. The surface drying time and actual drying time of the paint film are tested in accordance with GB / T1725-2007; the adhesion of the paint film is tested in accordance with GB / T5210-2006, using the circle test method (level 1 is the best and level 5 is the worst); the high temperature resistance (400°C) of the paint film is tested by placing a steel plate coated with -4 cups of primer in a 400°C oven for 2 hours and observing whether the paint film bubbles or peels (no change is acceptable). The above index test data are shown in Table 1 Table 1 Combining the test results of Examples 1-2 and Example 3, the heat resistance of Example 3 is higher than that of Example 1 and Example 2. This may be because the heat-resistant filler in Example 1 contains only ZrO2, and no zinc borate is added, so that ZrO2 inhibits the decomposition of silicate, but there is no B2O3 to cover the surface of the zinc powder, and the zinc volatilization rate increases, causing local blistering of the paint film after baking at 400°C for 2 hours; while the heat-resistant filler in Example 1 contains only zinc borate, and no ZrO2 is added, so that B2O3 covers the surface of the zinc powder, but there is no ZrO2 to inhibit the decomposition of silicate, and the silicate skeleton softens at 400°C, so that the paint film has moderate blistering after baking at 400°C for 2 hours; Example 3 adds ZrO2 and zinc borate in appropriate proportions at the same time. On the one hand, ZrO2 forms a stable tetragonal phase at high temperature, thereby inhibiting the high-temperature decomposition of the silicate skeleton. On the other hand, zinc borate decomposes at high temperature to produce B2O3, which reacts with Na2O in the sodium silicate solution to form a Na2B4O7 glassy layer, which covers the surface of the zinc powder and prevents zinc oxidation. The two work together to reduce the thermal conductivity of the coating, thereby improving the thermal insulation performance of the coating.
[0041] Combining the test results of Examples 4-5 and Example 3, the adhesion of Example 3 is better than that of Examples 4 and 5. This may be because in Example 4, the adhesion promoter contains only KH-560, and no E-44 epoxy resin is added. KH-560 only anchors the zinc powder and silicate, but no epoxy resin is cured and cross-linked, resulting in weak interface bonding; in Example 5, the adhesion promoter contains only E-44 epoxy resin, and no KH-560 is added. E-44 only cures silicate, but no silane anchors the zinc powder, resulting in weak interface bonding between the zinc powder and the substrate; in Example 3, because KH-560 and E-44 epoxy resin are added at the same time in an appropriate proportion, the epoxy group of KH-560 reacts with the hydroxyl group of the steel substrate to form a "substrate-silane" bonding layer, and the hydroxyl group (-OH) of the E-44 epoxy resin reacts with the Si-OH of the silicate to form a "silicate-resin" cross-linking layer, which then double-locks the zinc powder and the substrate, thereby improving the adhesion of the primer.
[0042] Combining the test results of Example 3 and Comparative Examples 1-3, the comprehensive performance of Example 3 is better than that of Comparative Examples 1-3. This may be because the quick-drying agent in Comparative Example 1 contains only zinc naphthenate without adding EDTA and titanium isopropoxide, resulting in excessive zinc naphthenate. 2+ The catalytic hydrolysis is too fast, generating a large amount of Si-OH but without EDTA to neutralize it, resulting in a decrease in pH value, stagnation of condensation, and obstruction of solvent volatilization. As a result, the silicate skeleton remains loose due to the lack of condensation reaction, and the zinc powder cannot be anchored, causing the residual air in the pores to expand due to heat. In Comparative Example 2, the fast-drying agent contains only EDTA without the addition of zinc naphthenate and titanium isopropoxide, resulting in excessive neutralization of H by EDTA. +, pH value is too high, no Zn 2+ Catalysis, the silicate hydrolysis rate is reduced, the silicate network is slowly constructed, the zinc powder is unevenly dispersed due to the lack of Si-OH anchoring, and the air remaining in the pores is heated and expanded, and the coating is slightly foamed when baked at 400°C. In Comparative Example 3, the quick-drying agent contains only titanium isopropoxide, without the addition of zinc naphthenate and EDTA, which results in the zinc powder being unable to be anchored to the silicate skeleton through Si-OH, and the silicate skeleton remains loose due to the lack of condensation reaction, and the solvent volatilization is severely hindered. When baked at 400°C, the zinc powder oxidizes and expands, causing large-scale foaming of the coating. Example 3 significantly improves the drying efficiency through the triple synergistic mechanism of "Lewis acid catalysis + alkaline environment maintenance + solvent volatilization acceleration", and through the mutual synergy of the components, the adhesion and drying speed of the inorganic zinc silicate workshop primer are improved at the same time.
[0043] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. A high adhesion quick-drying inorganic zinc silicate shop primer, characterized in that: The preparation raw materials include, by weight, 30-50 parts of modified zinc powder, 1.5-2.5 parts of modified graphite powder, 20-35 parts of sodium silicate solution, 5 parts of α-phase nano-Al2O3, 3-4 parts of a quick-drying agent, 3-5 parts of an adhesion promoter, 2.5-3.5 parts of a heat-resistant filler, 1-2 parts of a dispersant, 0.6-1.0 parts of a defoaming agent, and 10-20 parts of a diluting solvent. The quick-drying agent includes zinc naphthenate, EDTA, and titanium isopropoxide, and the mass ratio of the zinc naphthenate, EDTA, and titanium isopropoxide is 1:(0.2-0.3):(0.45-0.55).
2. The high-adhesion, quick-drying inorganic zinc silicate shop primer according to claim 1, wherein The preparation method of the modified zinc powder is as follows: pre-dispersing 30-50 parts of zinc powder and 0.5-1.5 parts of KH-560 in an ethanol solution, stirring and mixing at 60° C., filtering and drying to obtain the modified zinc powder with the surface coated with silane.
3. The preparation method of the high-adhesion quick-drying inorganic zinc silicate shop primer according to claim 1, wherein The preparation method of the modified graphite powder is as follows: pre-dispersing 1-3 parts of graphite powder and 0.45-0.65 parts of KH-560 in an ethanol solution, stirring and mixing at 60° C., filtering and drying to obtain the modified graphite powder with silane coated on the surface.
4. The high-adhesion, quick-drying inorganic zinc silicate shop primer according to claim 1, wherein The modulus of the sodium silicate in the sodium silicate solution is 3.5-3.
8.
5. The high-adhesion, quick-drying inorganic zinc silicate shop primer according to claim 1, wherein The adhesion promoter includes KH-560 and E-44 epoxy resins, and the mass ratio of the KH-560 to the E-44 epoxy resins is 3:
1.
6. The high-adhesion, quick-drying inorganic zinc silicate shop primer according to claim 1, wherein The heat-resistant filler is ZrO2 and zinc borate, and the mass ratio of ZrO2 to zinc borate is 2:
1.
7. The high-adhesion, quick-drying inorganic zinc silicate shop primer according to claim 1, wherein The dilution solvent includes propylene glycol methyl ether acetate and dimethyl carbonate, and the mass ratio of the propylene glycol methyl ether acetate to the dimethyl carbonate is 2:
1.
8. The high-adhesion, quick-drying inorganic zinc silicate shop primer according to claim 1, wherein The dispersant is a polycarboxylate dispersant.
9. The high-adhesion, quick-drying inorganic zinc silicate shop primer according to claim 1, wherein The defoaming agent is an organosilicon defoaming agent.
10. A method for preparing the high-adhesion, quick-drying inorganic zinc silicate shop primer according to any one of claims 1 to 9, characterized in that: The steps include: S1. Premixing of composite fillers: Add modified graphite powder, α-phase nano-Al2O3, heat-resistant filler, and dispersant into a high-speed disperser, premix and disperse vigorously to obtain premixed fillers; S2: Preparation of silicate-quick-drying agent system: Add zinc naphthenate and EDTA to the sodium silicate solution, stir and mix at 50°C, add titanium isopropoxide dropwise, and heat to 60°C to react to obtain a viscous silicate system solution; S3. Mixing: Add the premixed filler to the silicate system viscous liquid and mix well, then add the adhesion promoter and mix well, and then add the silicone defoamer to disperse vigorously; S4. Paint mixing: Add diluent solvent to adjust the viscosity to 18-22 seconds (25°C) for 4 cups.
Citation Information
Cited By
Environment-friendly water-based ink solvent with high drying efficiency and preparation method thereof
CN120842900A
A high adhesion coating and method of making the same
CN122483659A